Length‐weight relationships of eight fish from seagrass meadows in Wenchang, China - Xie, Meiling; Loh, Kar Hoe; Chen, Zehao; Liao, Jianji; Chen, Bin; Liu, Wenhua; Du, Jianguo (Wiley, 2020)
The length-weight relationships (LWRs) were studied for eight seagrass fish from Wenchang, China, using gill nets (150*1 m, mesh size 0.5 cm), including Gerres oblongus, Ambassis kopsii, Halichoeres nigrescens, Sillago aeolus, Yongeichthys criniger, Oxyurichthys tentacularis, Lethrinus haematopterus and Hypoatherina tsurugae, in November 2017, March and August 2018. Results suggest that mean LWR parameters b for these eight seagrass fish varied from 2.801 for L. haematopterus to 3.640 for A. kopsii, and r2 valued from.950 for L. haematopterus to 0.993 for H. nigrescens. This study will help us to better understand the ecological parameters these seagrass fish. © 2020 Blackwell Verlag GmbH